Pengaruh Penggunaan Gadget Terhadap Perilaku Belajar Siswa di SMA Negeri 2 Busungbiu - Astuti, Desak Made Dwi Widia; Dharmayasa, I Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This test was achieved to understand the influence of gadget use on student behavior at SMAN 2 Busungbiu. The test that will be used in this test is quantitative testing. Information collection is carried out by distributing questionnaires, and then the information mentioned is processed using the SPSS application. The information collected will be tested using descriptive statistical analysis, instrument testing, classical assumption testing, and hypothesis testing. The total respondents were 36 students. Obtaining hypothesis testing provides findings on the influence of gadget use on students' learning behavior at SMAN 2 Busungbiu based on tests carried out on students in 2023. by carrying out observations and interviews in the field with this, the learning attitudes of students at SMAN 2 Busungbiu are classified as good because they are influenced Most of the elements are that many students use gadgets properly, namely learning to use gadgets and communicating actively and directly even though they already have gadgets. In essence, gadgets can have a positive role if they are used properly, but gadgets can also have a negative role if the user misuses the gadget, depending on the individual student who uses the gadget.